2021
DOI: 10.1055/s-0041-1730303
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Anosmia in Non-hospitalized Patients in the COVID-19 Pandemic: A Cross-sectional Study

Abstract: Introduction It is now evident that the loss of smell and/or taste may be consistent accompanying symptoms of the SARS-CoV-2 infection. Objective To estimate the social behavior of recent anosmic non-hospitalized patients in the COVID-19 pandemic and to try to obtain the natural pattern in society in a cross-sectional study. Methods A cross-sectional study conducted on 4,860 patients with anosmia complaints during the COVID-19 pandemic. Patients who needed a consultation for an anosmia comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…This agrees with other studies done in our Middle East region and in other countries in Europe and in the USA. 4 7 10 11 Some of these studies suggested that the middle age group is more vulnerable to infection as they go out for work and studying, beside females having more concern about sense of smell than males. We found these explanations are reasonable for the wide agreement in different studies about the age and gender affected with anosmia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This agrees with other studies done in our Middle East region and in other countries in Europe and in the USA. 4 7 10 11 Some of these studies suggested that the middle age group is more vulnerable to infection as they go out for work and studying, beside females having more concern about sense of smell than males. We found these explanations are reasonable for the wide agreement in different studies about the age and gender affected with anosmia.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies 2 3 4 5 6 appeared in the last year, in a trial to discover and define the solid criteria for COVID-19 related anosmia. However, behavior among anosmic patients showed a large diversity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Anosmia and ageusia are prevalent symptoms of COVID-19 infection. 5 All of the previously mentioned facts, in turn, have made otolaryngologists even more susceptible than their counterparts. 6…”
Section: Introductionmentioning
confidence: 99%
“…4 Anosmia and ageusia are prevalent symptoms of COVID-19 infection. 5 All of the previously mentioned facts, in turn, have made otolaryngologists even more susceptible than their counterparts. 6 The present study aimed to find if COVID-19 had a different impact on ear, nose, and throat (ENT) physicians of various categories (residents, registrars, and consultants ) regarding many aspects of the quality of life (protection, training, financial, and psychological aspects) .…”
Section: Introductionmentioning
confidence: 99%